Educational Migration of Foreign University Monks in Mahachulalongkornrajavidyalaya University - Mongkonpipputporn, Punyavee; Seanboot, Sawaeng; Mangkhang, Charin; Dibyamandala , Jarunee (International Journal of Multidisciplinary in Management and Tourism, 2022)
Education is the basic life skills-fostering method for human beings to be ready to live for themselves and society. Furthermore, education can enhance life to be more prosperous combined with the social dimension that is rapidly changing. Travelling across borders is made more accessible by the fast development of information and communication technologies. These are the migration reasons for furthering their education. By examining the push and pull causes for educational migration, this article intends to investigate the notion of migration for the education of foreign university monks at Thai Buddhist universities. With the structured interview and descriptive data analysis, this article has combined material from documents, linked pieces of research, in-depth interviews, and a discussion with university monks of Mahachulalongkornrajavidyalaya University. The study’s findings are as follows: Eessential push factors of deciding to migrate for education to Thailand are, for instance, the limitation of the monks’ opportunities for education in their own countries; the country’s education system has not been developed to keep up with the changes in the world society and the financial problems in the family. These factors make these university monks decide to change their status from ordinary people to monks to be able to access education and reduce family expenses. Essential pull factors of the educational migration of the monks include a network of seniors who have graduated and those who are currently studying in the destination country, combined with Thai Buddhist universities’ tuition fees and the cost of living that are affordable. In addition, there are supportive religious social groups who support policies and educational opportunities for foreign university monks to raise their quality and integrate the education to benefit themselves and society.